Climate Change and Restoration of Tropical Forests - Soni, Prafulla (Indian Forester, 2003)
Fossil fuel consumption and global deforestation are the two major sources of rising carbon dioxide concentration and this is an important cause of enhanced greenhouse effect with implications on Global Climate Change The paper reviews the crucial role global forests play in initiating the atmospheric carbon dioxide increase and highlight the potential to mitigate approximately 15% of the world's Green House Gas emission. Forests act as a carbon sink for mitigating the green house effect and forest preservation is the best solution for carbon fixing and that extending the rotation period, Conversion to more natural forest and new afforestation of former agriculture land will all contribute to increased carbon storage. Carbon sequestration potential of tropical forests in particular has been discussed in detail with along with potential areas and strategies for restoration in India, so as to achieve maximum ecological benefits.